GOOD CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN SEBAGAI DETERMINAN NILAI PERUSAHAAN MELALUI PROFITABILITAS - Ardiani Ika Sulistyawati; Aprih Santoso; Putri Nur Pratiwi; Arief Himawan Dwi Nugroho (JURNAL LENTERA BISNIS, 2023)
The research objective is to analyze the effect of good corporate governance and company criteria on firm value through profitability. Using the purposive sampling method, the number of samples was 80 data from manufacturing companies in the consumer goods industry sector on the Indonesia Stock Exchange for the 2015-2019 period. The analysis technique uses regression and path analysis. This study proves that partially independent commissioners and profitability affect firm value, while profitability is only able to mediate between independent commissioners and institutional ownership on firm value. The adjusted R square of the profitability variable is 55.55% while the adjusted R square of the company value is 81.10%.Keywords: Good Corporate Governance, Corporate Values